Correspondence between alcohol use measured by a wrist‐worn alcohol biosensor and self‐report via ecological momentary assessment over a 2‐week period. (21st December 2022) - Richards, Veronica L.; Barnett, Nancy P.; Cook, Robert L.; Leeman, Robert F.; Souza, Timothy; Case, Stuart; Prins, Cindy; Cook, Christa; Wang, Yan
Abstract: Background: Transdermal alcohol biosensors measure alcohol use continuously, passively, and non‐invasively. There is little field research on the Skyn biosensor, a new‐generation, wrist‐worn transdermal alcohol biosensor, and little evaluation of its sensitivity and specificity and the day‐level correspondence between transdermal alcohol concentration (TAC) and number of self‐reported drinks. Methods: Participants ( N  = 36; 61% male, M age  = 34.3) wore the Skyn biosensor and completed ecological momentary assessment (EMA) surveys about their alcohol use over 2 weeks. A total of 497 days of biosensor and EMA data were collected. Skyn‐measured drinking episodes were defined by TAC > 5  μ g/L. Skyn data were compared to self‐reported drinking to calculate sensitivity and specificity (for drinking day vs. nondrinking day). Generalized estimating equations models were used to evaluate the correspondence between TAC features (peak TAC and TAC‐area under the curve (AUC)) and number of drinks. Individual‐level factors (sex, age, race/ethnicity, body mass index, human immunodeficiency virus status, and hazardous drinking) were examined to explore associations with TAC controlling for number of drinks. Results: Using a minimum TAC threshold of 5  μ g/L plus coder review, the biosensor had sensitivity of 54.7% and specificity of 94.6% for distinguishing drinking from nondrinking days. Without coder review, the sensitivity was 78.1% and the specificity was 55.2%. Peak TAC ( β  = 0.92, p  < 0.0001) and TAC‐AUC ( β  = 1.60, p  < 0.0001) were significantly associated with number of drinks. Females had significantly higher TAC levels than males for the same number of drinks. Conclusions: Skyn‐derived TAC can be used to measure alcohol use under naturalistic drinking conditions, additional research is needed to accurately identify drinking episodes based on Skyn TAC readings. Abstract : Transdermal alcohol biosensors measure alcohol use continuously, passively, and non‐invasively. There is little field research on the Skyn biosensor, a newer‐generation wrist‐worn device, and little evaluation of its sensitivity and specificity and the day‐level correspondence between transdermal alcohol concentration (TAC) and number of self‐reported drinks. Sensitivity and specificity varied by whether a minimum TAC alone or a minimum TAC plus coder review was used. TAC and number of self‐reported drinks were strongly correlated.